Genome architecture marked by retrotransposons modulates predisposition to DNA methylation in cancer - Estécio, Marcos R.H.; Gallegos, Juan; Vallot, Céline; Castoro, Ryan J.; Chung, Woonbok; Maegawa, Shinji; Oki, Yasuhiro; Kondo, Yutaka; Jelinek, Jaroslav; Shen, Lanlan; Hartung, Helge; Aplan, Peter D.; et al. (Genome Research, 2010)
Epigenetic silencing plays an important role in cancer development. An attractive hypothesis is that local DNA features may participate in differential predisposition to gene hypermethylation. We found that, compared with methylation-resistant genes, methylation-prone genes have a lower frequency of SINE and LINE retrotransposons near their transcription start site. In several large testing sets, this distribution was highly predictive of promoter methylation. Genome-wide analysis showed that 22% of human genes were predicted to be methylation-prone in cancer; these tended to be genes that are down-regulated in cancer and that function in developmental processes. Moreover, retrotransposon distribution marks a larger fraction of methylation-prone genes compared to Polycomb group protein (PcG) marking in embryonic stem cells; indeed, PcG marking and our predictive model based on retrotransposon frequency appear to be correlated but also complementary. In summary, our data indicate that retrotransposon elements, which are widespread in our genome, are strongly associated with gene promoter DNA methylation in cancer and may in fact play a role in influencing epigenetic regulation in normal and abnormal physiological states.